Understanding Personalized Recruitment Ads' Effectiveness: The Role of Personalization Type and Message Involvement. Issue 3 (2nd September 2022) - Pfiffelman, Jean; Pfeuffer, Alexander
Abstract: In response to the challenge of replacing retiring workers with new talent, recruitment ads on recruitment platforms are becoming increasingly sophisticated and personalized. On some platforms, recruiters can now integrate users' names and photographs into recruitment ads. Previous research has frequently found that ad personalization improves advertising effectiveness; however, personalization is not always an effective tactic, as personalization effects can be nuanced depending on the consumer and the ad's personalized elements. A between-subjects experiment ( N = 196) tested the effects of different types of recruitment ad personalization (integration of the recipient's name only or of both the recipient's name and photograph). This research found recruitment ads that were personalized with potential applicants' names and photographs increased organizational attractiveness for potential applicants who exhibited low involvement in the ad's message. In turn, their intentions to click on the ad and pursue the advertised job opportunity also increased.